Legal Framework for Combating Corruption in Nigeria -The Upstream Petroleum Sector in Perspective - OLUJOBI, Olusola Joshua (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Corruption in the Nigeria’s upstream petroleum sector is a serious concern and a major challenge facing Nigeria. Successive governments in Nigeria have fought corruption for decades with insignificant success. The paper examines how Nigeria’s anti-corruption legal regime can eradicate corruption in the sector and critically assesses our national anti-corruption laws. The writer adopts analytical method by placing reliance on secondary data such as academic journals, articles, statutes and textbooks. The writer discovers that, the challenge is not only with the existing anti-corruption legal regime but enforcement of the laws to achieve the desired objectives of combating corruption. The writer finds that, what is required on the part of the government in addition to legislative and institutional reform strategies is the strong political will to prosecute the alleged corrupt offenders and implementation of the letter and spirit of the law against corruption. The writer further discovers that, national anti-corruption laws are the most effective legal instruments that can address corruption in the sector. The paper therefore suggests some new measures that could be implemented to eradicate corruption such as improvement on some national laws to boost transparency, probity in the sector which is believed will reduce if not eliminate corruption in the sector.